Implementasi Model Problem Based Learning dalam Meningkatkan Hasil Pembelajaran - Tri Yoga Rahayu; Wirdati Wirdati; Mhd Zen (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to analyze teachers in applying model problem-based learning to improperly moving student learning outcomes in Islamic religious education subjects. This research uses a qualitative method with a case study approach, research data is taken through direct interviews with five informants (school principals, curriculum representatives, and two Islamic religious education teachers) and five students, who were selected using a purposive sampling technique. To strengthen the interview data, the writer made observations by being directly involved in the learning process in the classroom. All interview and observation data were then analyzed thematically using the Miles and Huberman method. Overall, The implementation of the Problem Based Learning (PBL) model in Islamic Religious Education learning on the material Exemplifying the Noble Nature of the Prophet at SMPN 22 Padang has fulfilled the syntax of Problem Based Learning (PBL). Educators have carried out each stage in accordance with the book guidelines, starting from orienting, organizing, developing an issue, displaying the work and evaluating learning outcomes. In improving learning outcomes educators have three ways. First, educators must collaborate on learning models. Second, educators provide additional time in assignments. Third, educators must master the materials, models and styles of solving problems in the implementation of the learning model.